Physical and mechanical properties of non-treated and NaOH-treated recycled polypropylene filled dried banana leaves composites - Narayanan, Thinakaran (2021)
Disposal of after-used plastic-based products has created worldwide problems on environmental pollution. This scenario has initiated the efforts to develop eco-friendly bio-composites products from the plastic wastes. In this research, recycled waste polypropylene (r-PP) was loaded with dried banana leaves (DBL) fibre, for r-PP/DBL green composites fabrication. The effects of sodium hydroxide (NaOH) treatment on DBL, effects of DBL fibre size and the effects of DBL fibre loading were studied based on the resulted mechanical, physical, thermal and their fracture morphological properties of produced r-PP/DBL composites. Due to the flexibility of plastic characteristic, the utilization of petroleum-based non-biodegradable plastic is turn out to be endless. This scenario has cultivated the important of post-production on waste plastic, combined with natural fibres, which are abundantly available and feasibly being consumed as a secondary phase of the polymer matrix composites (PMC). Dried banana leaves fibre has been utilized as a secondary phase for r-PP matrix. The r-PP was taken from an injection moulding post-operation and later was ground into fine particles by using an industrial crusher, while DBL is collected from the IKTBN Sepang reserved area and was ground into 10 μm and 30 μm of DBL fibre filler sizes. The particle size for DBL fibre has successfully confirmed by the characterization of Particle Size Analyser (PSA) and the DBL filler treatment was performed with sodium hydroxide (NaOH) at 80°C for 30 minutes of immersion period. The characterization for surface treatment on fibre has been confirmed via Fourier Transform Infrared (FTIR). Both r-PP matrix and DBL filler are blended with a melting device at the temperature of between 165°C to 185°C. The specimen for testing and analysis produced via an injection moulding process. For mechanical testing, that consists of the tensile, flexural and impact test as well as fractured surfaces morphological scanning, it was found that the treated DBL with 10 μm of DBL fibre size have increased tremendously the mechanical properties recorded at 45.2 MPa as compared than unfilled r-PP logged at 16.8 MPa. It was also proven by the thermal testing, that the treated and 10 μm of DBL fibre and 30 wt.% of DBL loading logged maximum at 178.29°C as compared than plain r-PP recorded at 160.25°C, has improved the thermal stability of this r-PP/DBL green composites. While stability in water absorption was also achieved by r-PP/DBL sample of this formulation. In overall, r-PP/DBL based composites have provided an absolute significant improvement as compared than the unfilled r-PP, which has dominated the best performances for almost of the entire performed tests. These findings underlined the potential of r-PP/DBL composite over the other leaf types fibre fillers, to establish improved filler-matrix interaction in composite, due to their better adhesion between the matrix and filler phases, which are beneficial for packaging application. In overall, r-PP/DBL green composite that was prepared through the blending process was able to offer remarkable mechanical and thermal characteristic effects between both matrix and filler.